Housing insecurity pathways to physiological and epigenetic manifestations of health among aging adults: a conceptual model - Bhat, Aarti C.; Fenelon, Andrew; Almeida, David M. (Frontiers in Public Health, 2025)
IntroductionHousing insecurity is a social determinant of health, as evidenced by its associations with mental, physical, and biological outcomes. The scientific understanding of the mechanisms by which housing insecurity is associated with health is still limited. This review adapts existing stress process models to propose a conceptual model illustrating potential pathways linking the specific stressor of housing insecurity to physiological and epigenetic manifestations of stress among aging adults.MethodsThis narrative review examines literature across multiple fields, including public health, psychology, and sociology. The literature selected for this review was identified through scientific databases including Web of Science, PubMed, JSTOR, and Google Scholar; primarily peer-reviewed empirical studies, literature reviews, and research reports published in English between 1981 and 2024; and principally based in the United States context. A synthesis of this literature is presented in a proposed conceptual model.ResultsThe literature supports the existence of two main predictors of housing insecurity: sociodemographic characteristics and the historical/current context. The main mediating pathways between housing insecurity and manifestations of stress include health behaviors, psychosocial resources, and structural resources. Moderating factors affecting the associations between housing insecurity and manifestations of stress include government assistance, chronic discrimination/unfair treatment, and individual differences. These interdependent mediating and moderating mechanisms affect stressor reactivity, a proximal manifestation of stress, which contributes to the physiological and epigenetic distal manifestations of stress in aging adults.Discussion and implicationsThe prevalence of housing insecurity among aging adults is growing in the United States, with significant implications for public health and health disparities, given the growing percentage of aging adults in the population. Further empirical testing of the mediating and moderating mechanisms proposed in the conceptual model will elucidate how housing insecurity is connected to health and provide insight into preventive strategies to ameliorate the adverse effects of housing insecurity on biological health among aging adults.